Scorecard approach to benchmarking organizational safety culture in construction. - Mohamed, Sherif
This paper promotes adopting the balanced scorecard tool to benchmark organizational safety culture in construction. It argues that this tool has the potential to provide a medium to translate the organization's safety policy into a clear set of goals across four perspectives: management, operational, customer, and learning. These goals are then further translated into a system of performance measures that could effectively communicate a powerful strategic focus on safety to the entire organization. Four perspectives have been developed to represent all stakeholders, thereby ensuring that a holistic view of safety is used for strategic reflection and implementation. The paper argues that by selecting and evaluating the appropriate measures, in each perspective, requirements can be identified, and actions to the identified goals can be aligned and facilitated. The proposed balanced scorecard approach should therefore enable construction organizations to pursue incremental safety performance improvements. Work-in-progress is briefly reported to give insight into the potential applicability of this approach.
Keywords: Construction